Effects of converted grassland on Hemiptera assemblages in surrounding rice fields. (20th November 2015) - Yasuda, Mika; Yasuda, Tetsuya
Abstract: Establishment of pastures for cattle grazing adjacent to rice crops may increase the abundance of rice pests, because some cultivated grass species are host plants to these insects. In this study, we investigated assemblages of Hemiptera potentially causing pecky rice in paddy fields in Japan, and the effects of converted grasslands on surrounding rice fields. We systematically sampled Hemiptera in five land‐use types, comprising riverside vegetation, rice fields, forage rice paddies, fallow fields and pasture in a fine‐scale agricultural mosaic. We also examined the abundance of the two main rice bug species, in relation to the proportion of pecky rice and distance to pasture. Converted pastures that contained cultivated bahia grass ( Paspalum notatum Flügge) and Italian ryegrass ( Lolium multiflorum Lam.), had the greatest abundance of three rice bug species; Stenotus rubrovittatus (Matsumura), Trigonotylus caelestialium (Kirkaldy) and Cletus punctiger (Dallas). The percentage of damaged pecky grains was significantly greater in rice fields near pasture (within 200 m) than in those farther away. Our study provides evidence that the main source of rice bugs in agricultural croplands was pasture; and suggests that managing food sources for these insect pests in pastures close to rice paddies could help reduce their detrimental impact on rice crops.